Effect of Intraoperative Lung-Protective Ventilation on Postoperative Pulmonary Complications in Non-ARDS Surgical Patients: A Prospective Multicenter Cohort Study - Ali Rezaei; Hossein Karimi; Zahra Mohammadi (CoinReads Media Prima, 2026)
Introduction: Postoperative pulmonary complications (PPCs) are among the most frequent adverse events after major surgery and drive substantial morbidity, prolonged hospitalization, and mortality. Although lung-protective ventilation (LPV) is well established in patients with acute respiratory distress syndrome (ARDS), its perioperative role in non-ARDS surgical patients remains incompletely defined. We evaluated the association between intraoperative LPV and PPCs in non-ARDS patients who underwent general anesthesia. Methods: In this prospective multicenter cohort study, adults undergoing elective non-thoracic, non-cardiac surgery were managed intraoperatively with LPV (tidal volume 6–8 mL/kg predicted body weight, PEEP 5–8 cmH₂O, selective recruitment maneuvers) or conventional ventilation (tidal volume 10–12 mL/kg, minimal PEEP). The primary outcome was the incidence of PPC within 7 postoperative days. Secondary outcomes included pneumonia, respiratory failure, length of stay, and 30-day mortality. Multivariable logistic regression was used to adjust for relevant confounders. Results: Of 1,000 patients, 500 received LPV and 500 conventional ventilation, with well-balanced baseline characteristics. PPCs occurred in 75 (15.0%) LPV patients versus 110 (22.0%) conventional patients (p=0.006). LPV was independently associated with lower PPC odds (adjusted odds ratio 0.60, 95% CI 0.42–0.85; p=0.004). Pneumonia was less frequent (6.0% vs. 10.0%, p=0.02) and hospital stay was shorter (median 5 days vs. 6 days, p=0.02). The ICU stay and 30-day mortality did not differ significantly. Conclusion: Intraoperative LPV was independently associated with fewer PPCs in non-ARDS surgical patients, alongside lower pneumonia rates and shorter hospitalization. These findings support the broader perioperative adoption of lung-protective ventilation to improve respiratory outcomes after surgery.